Discretion and accountability: An economic analysis of the ESMA judgment and the Meroni doctrine - Phedon Nicolaides; Nadir Preziosi (Intereconomics, 2014)
This paper assesses the effectiveness of the Meroni doctrine in the light of the recent judgment in the ESMA case. The first part explains in detail the problem of delegation of powers in the EU from the perspective of the principal-agent theory and complements it with the analysis of the trade-off between different levels of independence and accountability of agencies. A simple economic model is developed to illustrate the relationship between the independence and accountability of an agency. It shows that it is the accountability mechanism that induces the agent to act, rather than the extent of his independence. The paper also explains the intertemporal interactions between the principal and the agent on the basis of the incentives in place for the different players.
Keywords: 330; Gewaltenteilung; EU-Recht; Rechtsdurchsetzung; Prinzipal-Agent-Theorie; EU-Staaten